Viral infection, APOBEC3 dysregulation, and cancer - Lehle, Jake; Soleimanpour, Mohadeseh; Mokhtari, Samira; Ebrahimi, Diako (Frontiers in Genetics, 2024)
Viral infection plays a significant role in the development and progression of many cancers. Certain viruses, such as Human Papillomavirus (HPV), Epstein-Barr Virus (EBV), and Hepatitis B and C viruses (HBV, HCV), are well-known for their oncogenic potential. These viruses can dysregulate specific molecular and cellular processes through complex interactions with host cellular mechanisms. One such interaction involves a family of DNA mutators known as APOBEC3 (Apolipoprotein B mRNA Editing Catalytic Polypeptide-like 3). The primary function of these cytidine deaminases is to provide protection against viral infections by inducing viral mutagenesis. However, induction and dysregulation of A3 enzymes, driven by viral infection, can inadvertently lead to cellular DNA tumorigenesis. This review focuses on the current knowledge regarding the interplay between viral infection, A3 dysregulation, and cancer, highlighting the molecular mechanisms underlying this relationship.